The gender gap reloaded: is school quality linked to labor market performance? - Spyros Konstantopoulos; Amelie F. Constant (Institute for the Study of Labor (IZA), 2005)
This study examines the gender gap in wages of young adults in the late 1970s, mid 1980s, and 2000, in the middle and the tails of the wage distribution using quantile regression. We also examine the importance of school quality indicators in predicting future labor market performance. We conduct analyses for three major racial groups in the US: Whites, Blacks, and Hispanics. We employ base year and follow up data from two rich longitudinal studies: the National Longitudinal Study (NLS) of high school seniors in 1972 and the National Education Longitudinal Study (NELS) of eighth graders in 1988. Our results indicate that school quality is an important predictor of and positively associated to future wages for Whites, but it is less so for the two minority groups. We confirm significant gender disparities in wages favoring men across three surveys in the 1970s, 1980s, and 2000 that are unaccounted for. While the unexplained gender gap is evident across the entire wage distribution, it is more pronounced for Whites and less pronounced for Blacks and Hispanics. Overall, the gender gap in wages is more pronounced in higher paid jobs (top 10 percent) for all groups, indicating the presence of a n alarming glass ceiling.
Keywords: J16; J24; J31; 330; wages; gender differences; school quality; school effects; quantile regression; Lohndifferenzierung; Frauenarbeitslohn; Geschlechterdiskriminierung; Bildungsabschluss; USA